Review of the efficacy of AST-120 (KREMEZIN®) on renal function in chronic kidney disease patients. (1st January 2019) - Asai, Mayumi; Kumakura, Sei; Kikuchi, Mami
Abstract: AST-120 (KREMEZIN®) consists of oral, spherical carbon particles that adsorb uremic toxins and their precursors within the gastrointestinal tract, allowing them to be excreted in the feces. Uremic toxins such as indoxyl sulfate and p -cresyl sulfate are abundant in the blood of chronic kidney disease (CKD) patients and are related to the progression of both CKD and cardiovascular disease. AST-120 was approved in Japan in 1991 followed by Korea (2004), Taiwan (2007) and the Philippines (2010) for treating uremic symptoms and prolonging the time to initiation of dialysis in patients with progressive CKD. In this review, we provide an overview of the past clinical data on AST-120 from 1982 to 2013. The effect of AST-120 for renal events was not supported in the primary analysis of randomized clinical trials. However, post-hoc analyses revealed significant differences between the AST-120 and control groups in the second Japanese phase III trial and in the multinational Evaluating Prevention of Progression in CKD (EPPIC) trials. Furthermore, inhibitory effects on the progression of CKD, as represented by amelioration in the estimated glomerular filtration rate (eGFR) decline and serum creatinine (sCr) elevation were suggested. These results suggest that AST-120 delays the decline in renal function. In addition, AST-120 may prolong the time to the initiation of dialysis, especially in patients with progressive CKD. For further verification of the clinical efficacy of AST-120, future study inclusion criteria should be determined carefully, defining progressive CKD using markers such as declines in eGFR and sCr elevation.